Dinamika Seroprevalensi Virus Avian Influenza H5 pada Itik di Pasar Unggas Beringkit dan Galiran - Putra, I Gusti Ngurah Narendra; Dewi2, Ni Made Ritha Krisna; Suartha, I Nyoman; Mahardika, I Gusti Ngurah Kade (Veterinary Science and Medicine Journal; Vol 1 No 2 (2013), 2013)
Normal 0 false false false EN-US X-NONE X-NONE Live Bird Market (LBM) has a high potential for spreading Avian Influenza Virus (AIV) between fowls or from fowl to human. Up to now, a dinamic of avian flue incidents at many LBMs in Bali has not been reported. This research aimed to reveal a dynamic of seroprevalences of avian influenza in ducks at Beringkit (Badung) and Galiran (Kelungkung) LBMs. A total of 35 duck blood samples was collected from each of LBMs. Sampling was conducted monthly from March to August, 2012 . AIV antibody of duck serum was measured using Rapid Hemagglutination Inhibition (Rapid HI) test. Seroprevalence differences were analyzes with Chi-square (? 2 ) Nonparametric statistical test. The results showed that seroprevalences of AIV H5 in ducks at Beringkit and Galiran LBMs were very high, ranged from 68.6% to 100% and 65.7% to 97.1% respectively. A Dynamic of AIV H5 seroprevalences in ducks at Beringkit and Galiran LBM had a similar pattern, except in July 2012. This indicates that VAI H5 has been circulating for a long time and has been to be an endemic virus infection in ducks at LBMs in Bali. It can be suggested that an Avian Influenza Virus monitoring should be done continuously over a long period. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; line-height:150%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;}
Keywords: Avian Influenza Virus H5, Seroprevalence, Live Bird Market (LBM)